2014
DOI: 10.1056/nejmoa1312808
|View full text |Cite
|
Sign up to set email alerts
|

Mitral-Valve Repair versus Replacement for Severe Ischemic Mitral Regurgitation

Abstract: Background Ischemic mitral regurgitation is associated with a substantial risk of death. Practice guidelines recommend surgery for patients with a severe form of this condition but acknowledge that the supporting evidence for repair or replacement is limited. Methods We randomly assigned 251 patients with severe ischemic mitral regurgitation to undergo either mitral-valve repair or chordal-sparing replacement in order to evaluate efficacy and safety. The primary end point was the left ventricular end-systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
523
1
21

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 819 publications
(561 citation statements)
references
References 39 publications
16
523
1
21
Order By: Relevance
“…Fundamentally, the etiology of MV disease dictates repair feasibility and success. In a recently published, randomized controlled trial comparing MVR and MV‐repair for ischemic MV disease, there was no difference in the mortality rate between these procedures, but there was a higher incidence of recurrent MR after MV‐repair 2. The rate of recurrent MR and repeat surgery was very high in their multicenter study with only small groups of patients included from numerous institutions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fundamentally, the etiology of MV disease dictates repair feasibility and success. In a recently published, randomized controlled trial comparing MVR and MV‐repair for ischemic MV disease, there was no difference in the mortality rate between these procedures, but there was a higher incidence of recurrent MR after MV‐repair 2. The rate of recurrent MR and repeat surgery was very high in their multicenter study with only small groups of patients included from numerous institutions.…”
Section: Discussionmentioning
confidence: 98%
“…The role of MV‐repair for functional (ischemic) MV regurgitation is still under debate2, 3 and in rheumatic disease mainly MVR is performed, as MV‐repair is more complex in these patients and less durable 4. Due to the demographic changes in Western communities and a higher incidence of MV disease in the elderly population,5 the age of patients referred for MV surgery is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…MVR has been advocated over MVRP, but routine sparing of the sub-valvular apparatus has resulted in reproducible reductions in operative mortality after MVRP [48]. Many patient groups do not appear to benefit from MVR over MVRP, particularly patients with a greater burden of comorbidities [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…A large European study, the Amsterdam Center for Contemporary European Studies -A Two-Phase Observational Study of the MitraClip® System in Europe (ACCESS-EU) prospective nonrandomized trial, found 81.8% survival at 1 year and 78.9% Original Article pime pime pime pime p pi im me e EDITRICE outcomes following valve repair compared to degenerative MR [13]. Recently mitral valve replacement too has been demonstrated to have equivalent outcomes for functional MR patients in a randomized trial, even though earlier data has suggested a superior outcomes for MV repair [14]. However, an excess incidence of recurrent MR was noted at 1-year among patients undergoing MV repair [15].…”
Section: Studiesmentioning
confidence: 99%